1999
DOI: 10.5144/0256-4947.1999.490
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Apolipoprotein B Gene 3' Hypervariable Region Among Nationals of the Abu Dhabi Emirate and Comparisons with Other Populations

Abstract: Background: Among all the polymorphic markers available to date, a hypervariable region located in the 3' of the human apolipoprotein B gene has been extensively studied in global populations throughout the world. Patients and Methods: Using a polymerase chain reaction-based assay, we investigated the allele and genotype frequency distributions of the alleles (corresponding to repeats of a 30 base-pair core DNA sequence) of this hypervariable region in a group of 367 unrelated nationals (201 males, 166 females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…As mentioned in the earlier section that grouping of the alleles into different allelic model like five-allelic model proposed by Frossard and Lestringant, [25] , it was clear that group comprising of higher repeat alleles are more frequent in patients as compared to controls, an observation which was not so clearly visible when individual alleles were compared. Probable reason behind this trend lies in the high degree of allelic differentiation observed at ApoB3'HVR which might have hided the association signals among the two groups that belongs to same ethnicity, which became pronounced once these numerous alleles were grouped into three or five allelic structure.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…As mentioned in the earlier section that grouping of the alleles into different allelic model like five-allelic model proposed by Frossard and Lestringant, [25] , it was clear that group comprising of higher repeat alleles are more frequent in patients as compared to controls, an observation which was not so clearly visible when individual alleles were compared. Probable reason behind this trend lies in the high degree of allelic differentiation observed at ApoB3'HVR which might have hided the association signals among the two groups that belongs to same ethnicity, which became pronounced once these numerous alleles were grouped into three or five allelic structure.…”
Section: Discussionmentioning
confidence: 90%
“…E = EcoR1; M= MspI; X = XbaI * p = < 0.05, **p = <0.001 and *** p = < 0.0001 132 ± 35 120 ± 31 0.001 +, -refers to the presence and absence of cutting site for restriction endonuclease. E = EcoR1; M= MspI; X = XbaI * p = < 0.05, **p = <0.001 and *** p = < 0.0001 higher repeats (39-49), lower repeats (alleles (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) and median repeats (34-37) genotypes. It was observed that in extension of the genotype analysis, a significant association (p = 0.03) was observed between the higher repeats HVE 39-49 alleles and higher levels of Apo B (Table 3).…”
Section: Correlation Of Lipid Parameters With Apob Gene Polymorphismsmentioning
confidence: 99%
“…In contrast, the alleles AV3 and AV4 were relatively common to the controls but not to the MIS group. None of the 10 MIS subjects were homozygotes (p = .11, onesided, 95%CI = 0, 0.34, binomial distribution), whereas four of the eight control subjects (50%) were homozygous for alleles of APOB (p = .05, onesided, 95%CI = 0.17, 0.83, binomial distribution) but neither result was significantly different from the expected proportion of 0.2 (Boerwinkle, et al, 1989;Gene, Huguet, Sanchez-Garcia, Moreno, Corbella, & Mezquita, 1995;Frossard & Lestringant, 1999). However, the odds of the control group being homozygotes were significantly greater than the odds for the MIS group (p ≤ .03, 95%CI = 1.04, ∞, Fisher's exact test).…”
Section: Resultsmentioning
confidence: 89%
“…A total of 111 alleles were observed that ranged from seven to nine at seven STR loci (Tho1, TPO, FES, VWA, D4S243, DHFRP2 and VWF-1) whereas X11 alleles [11][12][13][14][15] were observed at the remaining three STR loci (D3S1358, D16S310 and F13A). In contrast, 16 alleles were observed only at ApoB 0 3HVR ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 111 observed alleles with as many as 16 alleles were observed at ApoB3 0 HVR, which is in accordance with other studies. 15 STR and VNTR markers are the most accepted regions of the human genome for assessing the levels of genetic diversity owing to their high mutation rates and high degree of polymorphism. 16 We also calculated different diversity parameters in order to quantify the range of polymorphism and genetic diversity.…”
Section: Discussionmentioning
confidence: 99%